Fractional Critical Shear Stress at Incipient Motion in a Bimodal Sediment - Yusron Saadi (Institute of Research and Community Outreach - Petra Christian University, 2008)
The objective of this research was to examine and to quantify the stability of mixed grain sediment beds previously exposed to different time length of uniform antecedent flow hydrograph. The assessment of bed stability was carried out based on the observation of temporal pattern of eroded sediment during two identical stability tests with time varying flow and higher peak discharge. This was linked to the movement of individual sediment fractions to obtain fractional critical shear stress in a bimodal sediment mixture. The stability tests suggest a considerable increased in the stability of individual grain. Longer exposure time by antecedent flow clearly had an influence in the increasing stability of the bed. The increased rate of fractional critical shear stress during stability tests varied between 16 % and 35 % in the coarse mode whilst in the fine mode the rate of increase varied between 27 % and 39 %.